The Economic Cost of a Poor Start to Life - Alderman, H. (2012)
A primary challenge for nutrition policy in low-income settings is to position nutrition as an investment rather than simply as a form of social spending that governments grant poor people to the degree that governments prioritize equity. Various economic models have produced estimates of the economic costs of malnutrition as a combination of the impact of malnutrition on mortality, on health care costs for the survivors, including those that manifest in adult years, and on the lost productivity attributable to malnutrition. However, these estimates often center on the costs of early mortality and are sensitive to assumptions on how to place a dollar cost on mortality. This study argues that even when focusing only on the productivity impact of malnutrition - clearly a lower bound of the full costs - the economic consequences of malnutrition are substantial. Stating this somewhat differently, the economic returns to preventing malnutrition are on a par with those investments generally considered at the heart of economic development strategies. Moreover, the body of evidence that has been accumulated to indicate these productivity gains is both substantial and robust.